Scientific conviction amidst scientific controversy in the transatlantic livestock and meat trade - Kastner, Justin; Powell, Douglas A.; Crowley, Terry; Huff, Karen (My University, 2008)
A century before bovine spongiform encephalopathy, Great Britain and North America grappled with an equally maddening disease in cattle: pleuro-pneumonia. The subject of a decades-long trade dispute in the nineteenth-century transatlantic region, pleuro-pneumonia attracted the attention of livestock farmers, diplomats, shipping moguls, veterinarians, public health regulators, and journalists. Scientific controversy aggravated the dispute; veterinary officials elaborated scientific opinions and regulatory orders amidst a prevailing confusion about microbiology and disease diagnostics. In this context emerged William Williams, an Edinburgh-based professor whose convictions spawned repeated disagreements with the British government’s diagnoses of pleuro-pneumonia in cattle from the United States and Canada.
Keywords: International agricultural trade; Food safety and security; History of science; Transatlantic trade; William Williams; Pleuro-pneumonia